PF.20 Intrauterine Transfusion For Rhesus Isoimmunisation in Scotland. (26th April 2013) - Wu, P; Cameron, AD; Gibson, JL; Ledingham, MA; Brennand, J
Abstract : Scottish intrauterine transfusion (IUT) cases for severe Rhesus isoimmunisation over 2002–2011 were reviewed. One hundred and forty-one pregnancies underwent 437 IUTs (mean 3.09, range 1–8). One hundred and thirty-one fetuses had middle cerebral artery Doppler peak systolic velocity values documented. All were >1.5 multiples of median prior to the first IUT, except for one that was inactive with a pericardial effusion. Twelve fetuses were hydropic. The haematocrit value prior to initial IUT was 20–29% in 38% of cases, whilst 27% had a haematocrit between 10–19%. Initial IUT was most commonly performed between 29–32 weeks gestation (35%) followed by 25–28 (26%) and 21–24 (21%) weeks gestation (range 17–25 weeks). In the majority of cases, fetus was transfused via umbilical vein (80%). Fourteen percent of transfusions were performed intrahepatically, 3% intraperitoneally and 3% were undocumented. Complications occurred in 58 (13%) IUTs and include cord haematoma, difficult procedure, bradycardia or tachycardia necessitating unplanned delivery, and in utero death (5 fetuses). The procedure-related loss rate was 1%. Birth outcomes were documented in 108 cases with a 94% live birth rate (n = 102). One patient underwent termination of pregnancy for trisomy 21. Short term postnatal outcomes were available for 86 neonates: 33 neonates required phototherapy only, with 31 cases requiring top-up transfusions. Nine neonates had an exchange transfusion and 9 had immunoglobulin or erythropoietin. Four neonates did not require any treatment. We conclude that our live birth and procedure-related loss rates are consistent with other published series. Parents need to be aware of potential postnatal therapies.